1987
DOI: 10.1021/bi00391a015
|View full text |Cite
|
Sign up to set email alerts
|

Deglycosylation studies on tracheal mucin glycoproteins

Abstract: Following several model experiments, conditions were developed for optimal deglycosylation of tracheal mucin glycoproteins. Exposure of rigorously dried material to trifluoromethanesulfonic acid at 0 degree C for up to 8 h results in cleavage of essentially all fucose, galactose, and N-acetylglucosamine, about 80% of the N-acetylneuraminic acid (NeuNAc), and a variable amount of N-acetylgalactosamine (GalNAc), the sugar involved in linkage to protein. Residual N-acetylneuraminic acid is sialidase susceptible a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 34 publications
3
27
0
Order By: Relevance
“…In parallel experiments, all of the glycosidases gave optimal digestion results when bovine fetuin was used as a control glycoprotein (data not shown). These results indicated that, although likely glycosylated, rmS5D-SRCRB-HA is also relatively resistant to glycosidase treatment, as has often been reported for some heavily glycosylated high M r proteins (25,26).…”
Section: Glycosylation Studiessupporting
confidence: 71%
“…In parallel experiments, all of the glycosidases gave optimal digestion results when bovine fetuin was used as a control glycoprotein (data not shown). These results indicated that, although likely glycosylated, rmS5D-SRCRB-HA is also relatively resistant to glycosidase treatment, as has often been reported for some heavily glycosylated high M r proteins (25,26).…”
Section: Glycosylation Studiessupporting
confidence: 71%
“…TFMSA nonselectively cleaves N-and O-linked sugars from the glycoproteins and deglcosylation of glycoproteins by TFMSA has been proven to be useful because the peptide backbone is left intact after treatment (22,23). Lewis rats immunized with CI-␣2 (22 kDa) after treatment with TFMSA (n ϭ 12) did not develop anterior uveitis (Fig.…”
Section: Posttranslational Modification Of the Ag Bestows Uveitogenicitymentioning
confidence: 99%
“…Chromosome mapping shows the two genes are located on different chromosomes, supporting a one-organ-one-gene hypothesis. On the other hand, a comparison of amino acid composition between airway and intestinal mucins (2,7,8) revealed a high degree of similarity. Furthermore, recent data showed that antibodies raised against the core protein ofbronchial mucin cross-reacted with mucin in intestinal goblet cells, strengthening the possibility of close structural homology between mucins from the two organs (13).…”
Section: Introductionmentioning
confidence: 99%
“…Biochemical analysis of purified mucins from various human tissues shows that they share several general properties: high molecular weight (> 106 D), high carbohydrate content (70-80%), and oligosaccharides consisting of N-acetyl galactosamine, galactose, fucose, sialic acid, and N-acetyl glucosamine (4). The latter are joined by O-glycosidic linkages to the core protein or apomucin, which is typically rich in hydroxyamino acids (2,(5)(6)(7). However, despite these similarities, extensive microheterogeneity exists, with mucins from various sources showing different stoichiometry of amino acids and sugars (compare 5, 7-9).…”
Section: Introductionmentioning
confidence: 99%